2021
DOI: 10.3389/fpubh.2021.741525
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Economic Growth: Theory and Simulation

Abstract: The outbreak of COVID-19 pandemic has caused profound consequences on world economy. In order to explore the long-term impact of the pandemic on economic growth and the effects of different policy responses, this paper combines economic theory with epidemiological model to construct an interdisciplinary model, in which labor supply is dynamically constrained by pandemic conditions. Analysis of model equilibrium suggests that outbreaks of infectious disease reduce labor supply and negatively affect economic out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 34 publications
0
17
0
2
Order By: Relevance
“…The COVID-19 pandemic has caused devastating impacts on global health and the economy [ 1 ]. As of 15 February 2022, 412.3 million confirmed cases of COVID-19 and approximately 5.8 million deaths have been reported worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has caused devastating impacts on global health and the economy [ 1 ]. As of 15 February 2022, 412.3 million confirmed cases of COVID-19 and approximately 5.8 million deaths have been reported worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the first stage (T = 0-16), the level of activity improves rapidly as the parameters expand. The indicator declines more significantly in line with the increased parameters in the second stage (T = [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and then tends to maintain stable growth with a reduced slope in the final stage (T = 36-69). In Figure 7c, the total social and economic benefit approximately maintains a linear increase over the whole duration of the pandemic, and in all cases, proportionally changes in line with the variation in the parameters.…”
Section: Sensitivity Analysis Of Model Parametersmentioning
confidence: 99%
“…The results also demonstrate that strict anti-virus policy measures have a limited effect in recovering from the harmful impact of the public health emergencies caused by the highly contagious virus. Xiang et al [ 32 ] found that although China’s public health policy at the initial stage was conductive to both virus containment and economic recovery, its marginal efficiency gradually waned. Only if the pandemic is controlled effectively will the economic stimulation policy function properly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[8][9][10][11][12][13] These measures had appreciable economic consequences for governments and families, resulting in an urgency to rapidly isolate and quarantine cases. 8,11,[14][15][16] The initial measures also necessitated governments to rapidly enhance their testing capacities, especially among low-and middle-income countries (LMICs), until reliable self-testing could be instigated. 8,9,17,18 However, there were concerns with the ability of LMICs to rapidly scale up the detection of SARS-CoV-2 using real-time reverse transcription polymerase chain reaction (RT-PCR) testing with often few fully equipped laboratories in the early stages of the pandemic, available resources to purchase reagents as well as potential stock-outs of reagents.…”
Section: Introductionmentioning
confidence: 99%